Validation study of a new reconstructed human epidermis model EPiTRI for in vitro skin irritation test according to OECD guidelines. (September 2021) - Liao, Chih-Ching; Wu, Cheng-Yi; Lin, Meng-Hsueh; Hsieh, Feng-Koo; Hsu, Lih-Tao; Chang, Shiun-Yin; Chen, Kuan-Jen; Huang, Hui-Ting; Hsu, Hui-Chun; Lin, Chiu-Hsing; Lin, Pei-Ju; Lai, Huey-Min; et al.
Abstract: Following the global trend of reducing animal testing, various reconstructed human epidermis (RHE) models for skin irritation test (SIT) have been developed, verified, validated and included in OECD TG 439. We developed a new RHE called EPiTRI and a SIT method using EPiTRI (EPiTRI-SIT model) following the OECD guidelines. EPiTRI possesses morphological, biochemical and physiological properties similar to human epidermis with well-differentiated multilayered viable cells with barrier function. The EPiTRI-SIT model was tested for 20 reference chemicals in Performance Standard of OECD TG 439 (GD 220), showing good predictive capacity with 100% sensitivity, 70% specificity and 85% accuracy. EPiTRI had sensitivity in detecting di-n-propyl disulphate, as an irritant chemical (UN GHS Category 2), whereas most validated reference methods detected it as a non-irritant. An international validation study of EPiTRI-SIT was conducted in four laboratories to confirm the within- and between-laboratory reproducibility, as well as predictive capacity. The phase I/II within-laboratory and between-laboratory reproducibility was 100%/95% and 95%, respectively. The overall sensitivity, specificity and accuracy of EPiTRI-SIT was 96%, 70% and 83%, respectively, which fulfilled the OECD criteria. Thus, EPiTRI, meets the criteria of Performance Standards of OECD TG 439 (GD 220) and is suitable for screening irritating chemicals in vitro. Highlights: Structure and function of new reconstructed human epidermis, EPiTRI, similar to human epidermis. International validation study of EPiTRI-SIT meets the acceptance criteria of OECD GD 220. EPiTRI-SIT classify di-n-propyl disulphide as an irritant whereas VRMs as non-irritant chemical.